2017
DOI: 10.3390/fluids2010007
|View full text |Cite
|
Sign up to set email alerts
|

Surface Quasi-Geostrophy

Abstract: International audienceOceanic and atmospheric dynamics are often interpreted through potential vorticity, as this quantity is conserved along the geostrophic flow. However, in addition to potential vorticity, surface buoyancy is a conserved quantity, and this also affects the dynamics. Buoyancy at the ocean surface or at the atmospheric tropopause plays the same role of an active tracer as potential vorticity does since the velocity field can be deduced from these quantities. The surface quasi-geostrophic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 154 publications
2
86
0
Order By: Relevance
“…The physical motivation for the inviscid SQG equation comes from the 3D quasi-geostrophic (QG) equation, which is an approximate description for the motion of a rotating stratified fluid with small Rosby number and small Froude number in which potential vorticity is conserved [41,27]. The SQG equation is obtained from the QG equation by assuming the potential vorticity is identically zero.…”
Section: Generalized Surface Quasi-geostrophic Equationmentioning
confidence: 99%
“…The physical motivation for the inviscid SQG equation comes from the 3D quasi-geostrophic (QG) equation, which is an approximate description for the motion of a rotating stratified fluid with small Rosby number and small Froude number in which potential vorticity is conserved [41,27]. The SQG equation is obtained from the QG equation by assuming the potential vorticity is identically zero.…”
Section: Generalized Surface Quasi-geostrophic Equationmentioning
confidence: 99%
“…Noting the significance of surface buoyancy gradients (a fact missed in the aforementioned first baroclinic mode framework), it has been suggested that surface QG (SQG) dynamics (Blumen, ; Held et al, ; Lapeyre, ) is a more appropriate framework for the oceans' surface (Klein et al, ; Lapeyre & Klein, ; Sasaki & Klein, ), and is reflected in the altimeter measurements (Lapeyre, ). Though the variance of buoyancy is transferred downscale (Pierrehumbert et al, ; Sukhatme & Pierrehumbert, ), even in the presence of an ambient buoyancy gradient (Sukhatme & Smith, ), surface KE actually flows upscale in SQG dynamics (Capet et al, ; Smith et al, ), consistent with the flux calculations using altimetry data.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13]). In the present article, we focus on the surface quasi-geostrophic (SQG) model [1,[14][15][16] obtained when α = 1. This model emerges in the study of atmospheric and oceanic dynamics when the active scalar is given by the temperature at one of the boundaries (e.g.…”
Section: Introductionmentioning
confidence: 99%